Bacterial Exposure Mediates Developmental Plasticity and Resistance to Lethal Vibrio lentus Infection in Purple Sea Urchin (Strongylocentrotus purpuratus) Larvae - Schuh, Nicholas W.; Carrier, Tyler J.; Schrankel, Catherine S.; Reitzel, Adam M.; Heyland, Andreas; Rast, Jonathan P. (Frontiers in Immunology, 2020)
Exposure to and colonization by bacteria during development have wide-ranging beneficial effects on animal biology but can also inhibit growth or cause disease. The immune system is the prime mediator of these microbial interactions and is itself shaped by them. Studies using diverse animal taxa have begun to elucidate the mechanisms underlying the acquisition and transmission of bacterial symbionts and their interactions with developing immune systems. Moreover, the contexts of these associations are often confounded by stark differences between ‘wild type’ microbiota and the bacterial communities associated with animals raised in conventional or germ-free laboratories. In this study, we investigate the spatio-temporal kinetics of bacterial colonization and associated effects on growth and immune function in larvae of the purple sea urchin (Strongylocentrotus purpuratus) as a model for host-microbe interactions and immune system development. We also compare the host-associated microbiota of developing embryos and larvae raised in natural seawater or exposed to adult-associated bacteria in the laboratory. Bacteria associated with zygotes, embryos, and early larvae are detectable with 16S amplicon sequencing, but 16S-FISH indicates that the vast majority of larval bacterial load is acquired after feeding begins and is localized to the gut lumen. The bacterial communities of laboratory-cultured embryos are significantly less diverse than the natural microbiota but recapitulate its major components (Alphaproteobacteria, Gammaproteobacteria, and Bacteroidetes), suggesting that biologically relevant host-microbe interactions can be studied in the laboratory. We also demonstrate that bacterial exposure in early development induces changes in morphology and in the immune system. In the absence of bacteria, larvae grow larger at the 4-arm stage. Additionally, bacteria-exposed larvae are significantly more resistant to lethal infection with the larva-associated pathogen Vibrio lentus suggesting that early exposure to high levels of microbes, as would be expected in natural conditions, affects the immune state in later larvae. These results expand our knowledge of microbial influences on early sea urchin development and establish a model in which to study the interactions between the developing larval immune system and the acquisition of larval microbiota.